Real-Life Cause-Effect Relations Between Urinary IL-6 Levels and Specific and Nonspecific Symptoms in a Patient With Mild SLE Disease Activity - Schubert, Christian; Seizer, Lennart; Chamson, Emil; König, Paul; Sepp, Norbert; Ocaña-Peinado, Francisco M.; Schnapka-Köpf, Mirjam; Fuchs, Dietmar (Frontiers in Immunology, 2021)
Background: Little is known about the real-time cause-effect relations between IL-6 concentrations and SLE symptoms. Methods: A 52-year-old woman with mild SLE activity collected her entire urine for the determination of IL-6/creatinine and protein/creatinine levels (ELISA, HPLC) for a period of 56 days in 12 h intervals (total: 112 measurements). Additionally, she answered questionnaires (VAS) on oral ulceration, facial rash, joint pain, fatigue and tiredness and measured her temperature orally twice a day. Time-series analyses consisted of ARIMA modeling and cross-correlational analyses (one lag = 12 h, significance level = p < 0.05). Results: Statistical analyses showed that increased urinary IL-6 concentrations preceded increased urinary protein levels by 36–48 h (lag3: r=+.225; p=.017) and that, in the opposite direction of effect, increased urinary protein preceded urinary IL-6 decreases by 12–24 h (lag1: r=–.322; p<.001). Moreover, urinary IL-6 increases co-occurred with increased oral ulceration (lag0: r=+.186; p=.049); after 48–60 h, however, IL-6 increases showed a strong tendency to precede oral ulceration decreases (lag4: r=–.170; n.s.). Increases in facial rash preceded decreases in urinary IL-6 after 84–96 h (lag7: r=–.215; p=.023). As to fatigue, increases in urinary IL-6 co-occurred with decreased fatigue (lag0: r=–.193; p=.042); after 84–96 h, however, IL-6 increases preceded fatigue increases (+lag7: r=+.189; p=.046). Finally, joint pain, tiredness and body temperature did not significantly correlate with urinary IL-6 concentrations in either direction of effect. Conclusions: The results of this evaluation point to real-life feedback mechanisms between immune activity and SLE symptoms. Comparison with a previous evaluation of this patient suggests a counterregulatory mechanism between Th1 activity and IL-6. These findings are preliminary and require replication to draw firm conclusions about the real-time relation between IL-6 and SLE disease activity.